2021
DOI: 10.1016/j.jocn.2021.02.012
|View full text |Cite
|
Sign up to set email alerts
|

SARS-CoV-2-associated first episode of acute mania with psychotic features

Abstract: Despite neuropsychiatric outcomes of SARS-CoV-2 infection are now under close scrutiny, psychoneuroimmunological characteristics of COVID-19 and precise pathophysiology of neuropsychiatric manifestations of the infection are still obscure. Moreover, there still exists a shortfall in demonstrating specific clinical manifestations of the brain involvement of the virus. Here, we presented a 33-year-old female patient with COVID-19, reporting acute-onset paranoid delusions symptoms, insomnia and irritability. Cran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
18
0
5

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 22 publications
(25 citation statements)
references
References 10 publications
(8 reference statements)
0
18
0
5
Order By: Relevance
“…Finally, 18 articles did not include individual level data and 7 articles were available as abstracts only. A total of 40 articles met inclusion criteria, comprising 48 individual patients from 17 countries ( Table 1 ) [ [25] , [26] , [27] , [28] , [29] , [30] , [31] , [32] , [33] , [34] , [35] , [36] , [37] , [38] , [39] , [40] , [41] , [42] , [43] , [44] , [45] , [46] , [47] , [48] , [49] , [50] , [51] , [52] , [53] , [54] , [55] , [56] , [57] , [58] , [59] , [60] , [61] , [62] , [63] , [64] ]. All but a single study [ 54 ] were in English and 20 (42%) cases were reported in the United States, where the largest proportion of these cases were documented.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, 18 articles did not include individual level data and 7 articles were available as abstracts only. A total of 40 articles met inclusion criteria, comprising 48 individual patients from 17 countries ( Table 1 ) [ [25] , [26] , [27] , [28] , [29] , [30] , [31] , [32] , [33] , [34] , [35] , [36] , [37] , [38] , [39] , [40] , [41] , [42] , [43] , [44] , [45] , [46] , [47] , [48] , [49] , [50] , [51] , [52] , [53] , [54] , [55] , [56] , [57] , [58] , [59] , [60] , [61] , [62] , [63] , [64] ]. All but a single study [ 54 ] were in English and 20 (42%) cases were reported in the United States, where the largest proportion of these cases were documented.…”
Section: Resultsmentioning
confidence: 99%
“…No lumbar puncture. Sen et al, 2021 [ 59 ] 33, F, TR Paranoid delusions that children were under effects of bad spirts and that husband having an affair. Also with insomnia, irritability, anxiety, dysphoric and manic Not reported None None +SARS-CoV-2 IgM.…”
Section: Resultsmentioning
confidence: 99%
“…mRNA vaccines contain nucleotides from the genetic code of the virus that encode a viral protein. This protein is a viral antigen that can cause neuropsychiatric symptoms such as autoimmune psychosis (anti- NMDAR, AMPAR, CAPR2 encephalitis) by rapidly increasing a pro-inflammatory response and activated autoimmune mechanism ( Pollak et al 2020 ; Sen, Yesilkaya, and Balcioglu 2021 ). Another hypothesis suggests that the inflammatory mechanisms caused by COVID-19 can trigger neuropsychiatric symptoms via thiamine deficiency.…”
Section: Casementioning
confidence: 99%
“…During the course of coronavirus disease-2019 (COVID-19) pandemic, many neuropsychiatric manifestations of the disease have been observed while the precise pathophysiology remains unknown ( Sen et al, 2021 ; Yesilkaya et al, 2021 ). New variants of coronavirus such as the 501.V2 and B.1.1.7 have emerged and obscurities in pathogenesis have increased even further with these variants.…”
mentioning
confidence: 99%